The Impact of Work Environment on Job Satisfaction and Stress among Haemodialysis Nurses in Malaysia: A Concept Paper - Yusuf, Zaima Mat (International Journal of Psychosocial Rehabilitation, 2020)
Haemodialysis(HD) work environment are known for their hefty work task and the patients require a high level of medical treatment and supervision. Most international studies related to nursing work environment focused at hospital level. Therefore, there’s a need to explore the HD work environment and its impact on job satisfaction and stress among the nurses in private or charity HD centres.According to Kanter’s theory, working environment with access to information, resources, support, and sense of empowerment among employees improves employees’ job satisfaction and organization outcome.Nurses felt stress when patient’s condition deteriorates, likewise, high workload and staff turnover, infectious diseases, coping with emergencies, patient behaviour and death as other sources of stress. This concept paper is to answer ‘What is the relationship between HD nurses’ perceptions of their work environments with job satisfaction and stress?’ A cross-sectional self-administered questionnaire will be employed to answer the research question. A regression model to test factors associated with HD nurse’s job satisfaction, stress and working environment. Understanding different aspects of work environment is vital in improving HD nurses job satisfaction and stress.